Answers

2014-11-03T22:17:02+08:00
X - y = 2 -----equation 1
2x - y = 1  ----equation 2
from equation 1
x - y = 2
x = y + 2  ----equation 1'
substitute equation 1' to equation 2
2x - y = 1
2(y+2) - y = 1
2y + 4 - y = 1
y = 1 - 4
y = -3
substitute y = -3 to equation 1'
x = y + 2
x = -3 + 2
x = -1
therefore the two lines intersect at (-1,-3)
for the x and y intercepts of each line:
line 1:
  x - y = 2
  for x-intercept, y=0
  x - 0 = 2
   x = 2
 for y-intercept, x=0
  x - y = 2
  0 - y = 2
     -y = 2
     y = -2
therefore the x and y intercepts of the first line are the points (2,0) and (0,-2) respectively
line 2:
2x - y = 1
  for x-intercept, y=0
2x - 0 = 1
  2x = 1
    x = 1/2
  for y-intercept, x=0
  2(0) - y = 1
    -y = 1
     y = -1
therefore the x and y intercepts of the second line are the points (1/2,0) and (0,-1) respectively
0